Fabrication and Characterization of Co-Doped Fe2O3 Spindles for the Enhanced Photo-Fenton Catalytic Degradation of Tetracycline - Wu, Liangpeng; Wang, Wenguang; Zhang, Shaohong; Mo, Dan; Li, Xinjun (ACS omega, 2021)
Co-doped Fe2O3 spindles with different Co contents were successfully fabricated by a facile one-step hydrothermal method. The crystalline structure, morphology, optical properties, and chemical state of the as-prepared catalysts before and after photo-Fenton reaction were characterized. Co2+ incorporated into the Fe2O3 lattice was confirmed by the above characterizations. Also, the photocatalytic and photo-Fenton catalytic performances of the samples were evaluated by the degradation of tetracycline (TC) under visible light irradiation in the absence/presence of H2O2. The results demonstrated that Co-doped Fe2O3 spindles exhibited better catalytic degradation performance in comparison with single Fe2O3 spindles, and the sample of Co(5%)-Fe2O3 spindles displayed the highest activity and best stability. The improvement of photo-Fenton activity might be attributed to two reasons: On the one hand, Co-doped Fe2O3 spindles not only formed the Fe vacancies to reduce the band gap but also could build up an internal electric field, which inhibits electron/hole pair recombination and facilitates the transfer of photoexcited charge carriers. On the other hand, the intrinsic Co2+/Co3+ redox cycling can accelerate the circulation between Fe2+ and Fe3+ in Co(5%)-Fe2O3 spindles to facilitate H2O2 consumption and produce more ·OH radicals for TC degradation.